Step-by-step explanation:
Given function is y = –x.
Substitute the values of x in the function and find the values of y.
y = –x
At x = –2,
y = –(–2) = 2
At x = –1,
y = –(–1) = 1
At x = 0,
y = –(0) = 0
At x = 1,
y = –1(1) = –1
At x = 2,
y = –(2) = –2
Now, substitute the values of y in the table.
The image of the table is attached below.
The first option,
both have to be negative, because they were originally both part of the one fraction, which was all negative.
Answer:
y=5
Step-by-step explanation:
Answer:
10/13 = 76.92%
Step-by-step explanation:
The question is missing some information because the underline is missing.
If we make table based on if the letter upper case (A) or lower case(a), and if the letter underlined(B) vs not underlined(b) the data will be:
A a
B 4 3 7
b 3 3 6
total 7 6
There are total of 13 letter there. The calculation will be:
P(A or B) = P(A) + P (B) - P(A and B) = (7 + 7 -4) / 13= 10/13 = 76.92%
Answer:D: 12
Step-by-step explanation:
D) The sum of any two sides of a triangle must be greater than the third side.